EXPLORING STUDENTS’ PERCEPTION ABOUT USING YOUTUBE EDUCATIONAL VIDEOS IN LEARNING NEW VOCABULARY - Farah Nadhira Hapsari; Sugeng Susilo Adi (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
Exploring Students' Perception About Using YouTube Educational Videos In Learning New Vocabulary, is a study to find students' perspectives in using educational videos on YouTube to learn new English vocabulary. The sampling method used in this quantitative research. Data collection was taken from the results of a questionnaire from 120 students from SMKN 11 Malang through the media Google Form. Researchers used google form to take a sample of qualified student questionnaires. The majority of them (94%) have watched YouTube Educational Videos and most of the students of SMKN 11 Malang said that YouTube Educational Videos were useful for their English learning media to learn students' vocabulary by means of Speaking, Listening, Reading and Writing. This study was analyzed quantitatively based on the facts of students who succeeded in learning vocabulary with YouTube Educational Videos with excellence which would later be constructed in the form of descriptive analysis. The results of the research prove that vocabulary learning using YouTube educational videos has many benefits and positive impacts for SMKN 11 students. Students will use various strategies to learn vocabulary while watching YouTube educational videos; Students use words in the appropriate grammatical form; Students do the pronunciation of words that are easily recognizable; Students recognize vocabulary in spoken and written form; Students do spelling words correctly; to develop English vocabulary. Teachers can develop vocabulary teaching with more flexible time by using YouTube educational videos.